The vital roles of blue foods in the global food system - Tigchelaar, Michelle; Leape, Jim; Micheli, Fiorenza; Allison, Edward H.; Basurto, Xavier; Bennett, Abigail; Bush, Simon; Cao, Ling; Cheung, William; Crona, Beatrice I.; DeClerck, Fabrice; Fanzo, Jessica; et al. (Elsevier, 2022)
Blue foods play a central role in food and nutrition security for billions of people and are a cornerstone of the livelihoods, economies, and cultures of many coastal and riparian communities. Blue foods are extraordinarily diverse, are often rich in essential micronutrients and fatty acids, and can often be produced in ways that are more environmentally sustainable than terrestrial animal-source foods. Capture fisheries constitute the largest wild-food resource for human extraction that would be challenging to replace. Yet, despite their unique value, blue foods have often been left out of food system analyses, policies, and investments. Here, we focus on three imperatives for realizing the potential of blue foods: (1) Bring blue foods into the heart of food system decision-making; (2) Protect and develop the potential of blue foods to help end malnutrition; and (3) Support the central role of small-scale actors in fisheries and aquaculture. Recognition of the importance of blue foods for food and nutrition security constitutes a critical justification to preserve the integrity and diversity of aquatic species and ecosystems.